2009
DOI: 10.2967/jnumed.109.062208
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG and 18F-FLT Uptake Early After Cyclophosphamide and mTOR Inhibition in an Experimental Lymphoma Model

Abstract: To be a reliable predictor of response, tracer uptake should reflect changes in the amount of active tumor cells. However, uptake of 18 F-FDG, the most commonly used PET tracer, is disturbed by the inflammatory cells that appear early after cytotoxic therapy. The first aim of this study was to investigate whether 39-18 F-fluoro-39-deoxy-L-thymidine ( 18 F-FLT), a marker of cellular proliferation, is a better tracer for response assessment early after cytotoxic therapy. A second objective of this study was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…It is likely that an influx of inflammatory cells, which can be observed already 48 hours after mTOR inhibition (42), contributes to higher FDG-uptake in vivo. Because FDG-uptake of inflammatory cells is similar or may even exceed that of tumor cells, transient increase in stromal reaction may result in overestimation of viable tumor (43).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that an influx of inflammatory cells, which can be observed already 48 hours after mTOR inhibition (42), contributes to higher FDG-uptake in vivo. Because FDG-uptake of inflammatory cells is similar or may even exceed that of tumor cells, transient increase in stromal reaction may result in overestimation of viable tumor (43).…”
Section: Discussionmentioning
confidence: 99%
“…However, some false-positive findings have been reported for 18 Because of these limitations of 18 F-FLT PET for tumor staging, monitoring tumor response to therapy is perhaps the most promising clinical application of 18 F-FLT PET. A series of animal studies has indicated that 18 F-FLT uptake decreases rapidly in response to radiotherapy (9,10), cytotoxic chemotherapy (11,12), and various protein kinase inhibitors (13)(14)(15)(16). In some (9,11,12,15) but not all of these studies (10,13,14), changes in 18 F-FLT uptake better reflected the effects of therapy than did changes in 18 F-FDG uptake.…”
Section: Imaging Of Tumor Cell Proliferationmentioning
confidence: 99%
“…The most frequently employed radiotracer was 18 (19,20). To our knowledge, there have been no other previously reported PET studies in mice inoculated orthotopically with patient-derived colon cancer cells.…”
Section: Introductionmentioning
confidence: 99%